Effect of hemodialysis session on acute changes in inflammatory and cardiovascular risk biomarkers - Lavín Gómez, Bernardo-Alio; García Unzueta, María-Teresa; Guerra Ruiz, Armando-Raúl; San-Martín, Sonia Pérez; Berja, Ana; Rodríguez, Natalia Fañanás; Espejo, Sara Díez; Leguina, Domingo González-Lamuño (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Inflammation is associated with enhanced cardiovascular risk profile and increased cardiovascular mortality in end-stage kidney disease patients undergoing hemodialysis. Mechanisms of activated acute phase reaction in patients on chronic hemodialysis remain to be identified. As successful treatment of the inflammatory condition in these patients may improve long-term survival, we studied potential changes in different inflammatory biomarkers of cardiovascular risk in end-stage kidney disease patients after a mid-week hemodialysis session. Methods: Inflammatory biomarkers of cardiovascular risk (cystatin-C, homocysteine, C-reactive protein, procalcitonin, pentraxin-3, serum amyloid-A) and atherogenic plasma lipoproteins (Lipoprotein(a), cholesterol low and high density lipoproteins) were studied in 21 end-stage kidney disease patients previously and after a mid-week hemodialysis session. Results: We found a significant reduction in serum levels of low molecular weight molecules: cystatin-C (5.56 to 1.85 mg/L, 66.73%, p < 0.001), homocysteine (22.85 to 13.25 µmol/L, 42.01%, p < 0.001) and procalcitonin (0.788 to 0.457 ng/mL, 42.01%, p < 0.001). Large molecules as C-reactive protein (9.70 to 9.90 mg/L, 2.06%, p = 0.022) and pentraxin-3 (1.67 to 4.28 ng/mL, 156%, p < 0.001) increased, but serum amyloid-A decreased (15.90 to 12.70 mg/L, 20.13%, p < 0.05). There was no change in Lipoprotein (a) levels. Conclusion: Pentraxin-3 was a more specific inflammatory vascular marker than C-reactive protein, and the best inflammatory marker associated with hemodialysis. Homocysteine, procalcitonin and the other small proteins could be released and removed during hemodialysis session. Further studies are needed to understand the behavior and significance of these markers after successive hemodialysis.